Awareness of Cybersecurity: A Case Study in a Logistics Organizations - Jamaludin, N.A.A.; Abdul Rauf, U.F.; Awang, N.F.; Chuen. L, Chen (JOIV : International Journal on Informatics Visualization, 2025)
Sweeping digital transformation provides the logistics and supply chain industry with technology to overcome disruptive norms and simultaneously attract cybercriminals with opportunities and threats to infiltrate organization data. Cybersecurity and information security are crucial platforms for logistics and supply chains as they are required from time to time to keep up with the evolving cyber threats, and the best way to achieve such resilience is through a cyber-aware workforce. This study aims to understand employees’ cybersecurity awareness in a logistics organization based on human factors such as employees’ level of awareness, attitude, and knowledge and examine the high and very significant correlation between demographic profiles. An online survey questionnaire was constructed and distributed to employees via web-based tools and physical copy handouts. This approach was used to gather data for the objectives of the study. The participants were divided into the support group and the distribution group, totaling 50 respondents who had completed the survey. Statistical Product and Service Solutions (SPSS) is used to analyze the data gathered from the online survey and physical copies. The method uses descriptive analysis and cross-tabulation to determine the most significant and correlated variables. Based on the results obtained, although most respondents had positive results, it is concerning when a small percentage demonstrates a lack of awareness, knowledge, and a high-risk attitude toward cybersecurity within the organization. As for future implications, it is suggested that a mix of quantitative and qualitative approaches be used to support and increase the reliability of the research.